(untitled) (International Journal of Business, Economics and Management, 2019)
This study aims to evaluate cashless systems as a means of payment and receipt in Ghana. Specifically, the study sought to identify the modes of cashless systems in use and evaluate the level of implementation. A quantitative approach was adopted and primary data was gathered from 345 respondents knowledgeable in cashless systems using a structured questionnaire. Secondary data on cashless systems transactions between 2013 and 2017 were obtained from the Bank of Ghana. Data were analysed quantitatively using SPSS and presented using tables and charts. The findings reveal that the value of transactions made through cashless systems is on the rise. The use of cheques continues to be the dominant system in place at the end of 2017. The study found that mobile money services are penetrating the market at a pace faster than all other cashless payment and receipt modes. Internet banking is another emerging area that is also fast gaining ground. Debit/credit cards, E-zwich and Electronic funds transfers are not fully used in day to day transactions. Point of Sale terminals are rarely available at local shops to promote the use of cards in making purchases. The study found convenience, time savings and security from physical attacks to be the key benefits of cashless systems. Low literacy serves as major challenge to cashless system implementation. Based on these findings, it is recommended that local shops and supermarkets be assisted to adopt cashless receipt systems. The ease of finding shops that accept e-payments for items will reduce the desire in carrying cash for transactions.